1996
DOI: 10.1007/bf00434547
|View full text |Cite
|
Sign up to set email alerts
|

The ceramic cup type Lindenhof

Abstract: We followed up 10-14 years postoperatively the 106 ceramic cups type 'Lindenhof' that were implanted in the years 1978-1982. In that time, only 7 (6.6%) cups had to be changed due to aseptic loosening. Examination of 73 (68.9%) cups showed that only 4% of the patients were dissatisfied. Using the score of Merle d'Aubigne, we found 89% good and very good results. The high number of cup migrations reported by other authors could not be verified: we saw 35% in all. Most of them appeared in the early postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Sample numbers (number of hips) are: Bohm and Bosch 1998: 22 at start n=264; 10 years n=9; 11 years (final) n=2. Gierse et al ., 1996: 23 at start n=106; at 14 years (final) n=73. Neuerburg et al , 2012: 20 at start n= 1270; at 10 years (final); at 5 years n=1024; at 10 years (final) n=286.…”
Section: Figurementioning
confidence: 99%
“…Sample numbers (number of hips) are: Bohm and Bosch 1998: 22 at start n=264; 10 years n=9; 11 years (final) n=2. Gierse et al ., 1996: 23 at start n=106; at 14 years (final) n=73. Neuerburg et al , 2012: 20 at start n= 1270; at 10 years (final); at 5 years n=1024; at 10 years (final) n=286.…”
Section: Figurementioning
confidence: 99%
“…Gierse et al [10] also reported an initial or short-term postoperative migration in 35% of the patients receiving this ceramic cup.…”
Section: Introductionmentioning
confidence: 84%